Evaluasi Pengawasan Peredaran Rokok Ilegal oleh Seksi Penindakan dan Penyidikan KPPBC Malang.: Indonesia - Salsabila, Nadiyah Putri; Irianto, Gugus (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The circulation of illegal cigarettes remains a serious problem that harms state revenue, creates unfair business competition, and weakens excise law enforcement. This study aims to evaluate the effectiveness of monitoring illegal cigarette circulation conducted by the Enforcement and Investigation Division of the Malang Customs and Excise Office based on the Director General of Customs and Excise Regulation Number PER-8/BC/2024 concerning Intelligence and Monitoring Procedures. A descriptive qualitative approach was employed through field observations, interviews with intelligence and enforcement officers, and analysis of institutional documentation. Results indicate that the monitoring system has been implemented systematically through six stages: intelligence planning, data collection, assessment, analysis, information distribution, and continuous evaluation and updating of data. Operational strategies include patrol activities, market operations, whistleblower utilization, e-monitoring systems, and the “Gempur Rokok Ilegal” campaign. Notable achievement was recorded during January–July 2025, with the seizure of approximately 3.2 million illegal cigarette sticks, preventing potential state revenue losses exceeding Rp1 billion. However, supervision still encounters several obstacles, including limited human resources, insufficient surveillance technology, extensive territorial coverage, incomplete inter-agency coordination, and low public law awareness. To address these challenges, KPPBC Malang has strengthened cross-sector collaboration, adopted intelligence-based monitoring supported by data analytics, intensified community education programs, and optimized Tobacco Excise Revenue Sharing Funds (DBHCHT) to enhance operational capacity. Overall, the monitoring efforts are considered effective but require continuous improvement and technological integration to achieve sustained and comprehensive control of illegal cigarette distribution.